SPECIFIC CHARACTERISTICS OF IMPROVING TEACHING METHODOLOGY BASED ON DEVELOPMENTAL EDUCATION OF NATURAL SCIENCES IN PRIMARY GRADES - Khoshbok NORBOTAEV; Khusniddin BOBOMURODOV (Scholar Express Journal, 2022)
In the article, the nature and features of improving the teaching methodology based on the developmental education of primary classes are determined in accordance with the main goal of the educational paradigm and qualification requirements, as well as the scientific development of students' creativity, competence and natural-scientific outlook. to carry out research work, to effectively use the results of practical importance, to improve the educational system based on developmental education, to strengthen its national ground, to raise active, skilled, competent and competent students to the level of world standards It is stated that it is possible to increase the quality and efficiency of education in the improvement of the teaching methodology based on the issues of development and the development of primary school classes.
Keywords: Developmental education; primary class; education; interactive